Biomechanical analysis of the Universal 2 implant in total wrist arthroplasty: a finite element study. Issue 10 (27th July 2017) - Gislason, M. K.; Foster, E.; Bransby-Zachary, M.; Nash, D. H.
Abstract: Little is known about the mechanics of in vivo loading on total wrist prostheses where many studies have looked at the mechanics of other types of arthroplasty such as for the hip and the knee which has contributed to the overall success of these types of procedures. Currently surgeons would prefer to carry out arthrodesis on the wrist rather than consider arthroplasty as clinical data have shown that the outcome of total wrist arthroplasty is poorer than compared to the hip and knee. More research is needed on the loading mechanisms of the implants in order to enhance the design of future generation implants. This study looks at the load transfer characteristics of the Universal 2 implant using a finite element model of a virtually implanted prosthesis during gripping. The results showed that the loading on the implant is higher on the dorsal and ulnar aspect than on the volar and radial aspect of the implant. The whole load is transmitted through the radius and none through the ulna.